Toxicological studies of ethanol leaf extract of cassia fistula on haematological and biochemical parameters of Wistar albino rats (2019)
Aim: Cassia fistula L. (Fabaceae) is an annual herbaceous plant used in folklore medicine for the treatment of a wide range of conditions such as astringent, febrifuge and purgative. But the effects have not been well elucidated. This study was aimed at investigating the effect of Cassia fistula on haematological and serum biochemical indices in Wistar rats. Materials and Methods: Phytochemical constituents from the ethanol extract of C. fistula were identified by qualitative techniques and gas chromatography-mass spectroscopy (GC-MS). Twenty male Wistar rats were randomly assigned into four groups of five rats each. Group A, the control, received 0.2ml of corn oil each daily for 7 days; Group B rats were given 100mg/kg b.w. of Cassia fistula extract, Group C were given 200mg/kg b.w. of the extract while the rats in Group D were given 300mg/kg b.w ethanol extract of Cassia fistula orally for 7 days. Blood samples were collected afterward for determination of haematological parameter while plasma biochemistry was carried on the plasma after 7 days of treatment with the extract. Frequency of micronucleated polychromatic erythrocytes was also determined from blood Giemsa stained smear. Results: Qualitative analyses revealed the presence of tannins, saponins, alkaloids, anthraquinones, cardenolides, and phenols. In GC-MS analysis, 19 compounds including phytol, oleic, myristic acids etc. were detected from the ethanol leaf extract of C fistula. Oral treatment of Cassia fistula was found to be safe up to the 300mg/kg b.w dose because haematological and biochemical parameters in treated rats were comparable to the untreated control. In fact, the extract showed nephroprotective and hepatoprotective activity at 200 mg/kg. Conclusion: This study showed that ethanol leaf extract of Cassia fistula is not toxic upt to 300 mg/kg b.w, instead the extract showed some protective effects on liver and kidney functions at the 200 mg/kg b.w dose. This dosage should therefore be explored further for therapeutic purposes.